Central expression of synaptophysin and synaptoporin in nociceptive afferent subtypes in the dorsal horn - Chung, Jumi (Sci Rep, 2019)
Central sprouting of nociceptive afferents in response to neural injury enhances excitability of nociceptive pathways in the central nervous system, often causing pain. A reliable quantification of central projections of afferent subtypes and their synaptic terminations is essential for understanding neural plasticity in any pathological condition. We previously characterized central projections of cutaneous nociceptive A and C fibers, selectively labeled with cholera toxin subunit B (CTB) and Isolectin B4 (IB4) respectively, and found that they expressed a general synaptic molecule, synaptophysin, largely depending on afferent subtypes (A vs. C fibers) across thoracic dorsal horns. The current studies extended the central termination profiles of nociceptive afferents with synaptoporin, an isoform of synaptophysin, known to be preferentially expressed in C fibers in lumbar dorsal root ganglions. Our findings demonstrated that synaptophysin was predominantly expressed in both peptidergic and IB4-binding C fiber populations in superficial laminae of the thoracic dorsal horn. Cutaneous IB4-labeled C fibers showed comparable expression levels of both isoforms, while cutaneous CTB-labeled A fibers exclusively expressed synaptophysin. These data suggest that central expression of synaptophysin consistently represents synaptic terminations of projecting afferents, at least in part, including nociceptive A-delta and C fibers in the dorsal horn.